Uncovering Hidden Lineages in Korean Foliicolous Lichens (Strigulaceae, Strigulales): Discovery of a New Cryptic Genus and Species - Jung-Jae Woo; Robert Lücking; Seung-Yoon Oh; Yong-Chull Jeun; Jae-Seoun Hur (Mycobiology, 2025)
Foliicolous or leaf-dwelling lichens are mostly found in (sub-)tropical rainforests; due to their sensibility to environmental changes, they may serve as biological indicators for rainforest ecosystems. In Korea, the northward shift of subtropical conditions due to global climate change has emphasized the importance of understanding foliicolous lichen diversity and distribution, as they are now increasingly found in these latitudes. This study revises the taxonomy and distribution of foliicolous species in the family Strigulaceae in Korea through ITS-based identification and multigenetic analyses using four additional genetic markers (SSU, LSU, TEF1-α, and RPB2). The results support Racoplaca pelta sp. nov. and Reticula ambigua gen. nov. et sp. nov. as distinct phylogenetic lineages. Newly obtained ITS sequences confirmed that previously misidentified specimens of Strigula subelegans (KoLRI016349 and KoLRI016333) and Racoplaca melanobapha (KoLRI016334) correspond to S. multiformis and R. pelta, respectively. In addition, the distribution of Strigulaceae, once known only from Jeju Island within Korea, was found to extend to four additional southern islands: An, Ga-geo, Geo-mun, and Gwan-mae.